Stimulation of glycolysis promotes cardiomyocyte proliferation after injury in adult zebrafish. (9th July 2020) - Fukuda, Ryuichi; Marín‐Juez, Rubén; El‐Sammak, Hadil; Beisaw, Arica; Ramadass, Radhan; Kuenne, Carsten; Guenther, Stefan; Konzer, Anne; Bhagwat, Aditya M; Graumann, Johannes; Stainier, Didier YR
Abstract: Cardiac metabolism plays a crucial role in producing sufficient energy to sustain cardiac function. However, the role of metabolism in different aspects of cardiomyocyte regeneration remains unclear. Working with the adult zebrafish heart regeneration model, we first find an increase in the levels of mRNAs encoding enzymes regulating glucose and pyruvate metabolism, including pyruvate kinase M1/2 (Pkm) and pyruvate dehydrogenase kinases (Pdks), especially in tissues bordering the damaged area. We further find that impaired glycolysis decreases the number of proliferating cardiomyocytes following injury. These observations are supported by analyses using loss‐of‐function models for the metabolic regulators Pkma2 and peroxisome proliferator‐activated receptor gamma coactivator 1 alpha. Cardiomyocyte‐specific loss‐ and gain‐of‐function manipulations of pyruvate metabolism using Pdk3 as well as a catalytic subunit of the pyruvate dehydrogenase complex (PDC) reveal its importance in cardiomyocyte dedifferentiation and proliferation after injury. Furthermore, we find that PDK activity can modulate cell cycle progression and protrusive activity in mammalian cardiomyocytes in culture. Our findings reveal new roles for cardiac metabolism and the PDK‐PDC axis in cardiomyocyte behavior following cardiac injury. Synopsis: Cardiac metabolism regulates cardiomyocyte dedifferentiation and proliferation in injured zebrafish hearts as well as cell cycle progression in mammalian cardiomyocytes. Cardiomyocyte‐specific loss‐ and gain‐of‐function analyses reveal an essential role for glycolysis during cardiac regeneration. Glycolysis stimulates mammalian cardiomyocyte cell cycle progression. Enhanced glycolysis by PDK3 overexpression leads to increased cell cycle regulator mRNA levels. Abstract : Cardiac metabolism regulates cardiomyocyte dedifferentiation and proliferation in injured zebrafish hearts as well as cell cycle progression in mammalian cardiomyocytes.